Extended Peritoneal Dialysis and Renal Recovery in HIV-Infected Patients with Prolonged AKI: A Report of 2 Cases - Donlawat Saengpanit; Pongpratch Puapatanakul; Piyaporn Towannang; Talerngsak Kanjanabuch (Case Reports in Nephrology)
Peritoneal dialysis (PD) has recently been established as a treatment option for renal replacement therapy (RRT) in patients with acute kidney injury (AKI). Its efficacy in providing fluid and small solute removal has also been demonstrated in clinical trials and is equivalent to hemodialysis (HD). However, effect of RRT modality on renal recovery after AKI remains a controversy. Moreover, the setting of human immunodeficiency virus- (HIV-) infected patients with AKI requiring RRT makes the decision on RRT initiation and modality selection more complicated. The authors report here 2 cases of HIV-infected patients presenting with severe AKI requiring protracted course of acute RRT. PD had been performed uneventfully in both cases for 4–9 months before partial renal recovery occurred. Both patients eventually became dialysis independent but were left in chronic kidney disease (CKD) stage 4. These cases highlight the example of renal recovery even after a prolonged course of dialysis dependence. Thus, PD might be a suitable option for HIV patients with protracted AKI.